Design of thermoelectric devices for extracting foreign objects from the human body by freezing - O. V. Evdulov; A. M. Nasrulaev; R. Sh. Kazumov (Вестник Дагестанского государственного технического университета: Технические науки, 2021)
Objectives.The  purpose  of  the  article  is  to  consider  the  designs  of thermoelectric  devices  (TEC)  for  extracting  foreign  objects  (IO)  from  the  human  body  by freezing with various options for removing heat from the hot junctions of the thermoelectric module (TEM).Method. Modifications of thermoelectric devices are described for extracting the IO from the human body by freezing it to a special probe. Their technical design differs in the way of heat removal from the TEM hot junctions, for which air heat removal, melting working substances and preliminary cooling of the radiator are used. The basic relationships for calculating the technical means intended for the removal of heat from the hot junctions of the TEM are presented.Result. The graphs of the dependence of the temperature change of the TEM hot junctions in time are obtained for different values of its heat output when using an air heat removal system and the time of complete penetration of various working substances used in the device.Conclusion. The data obtained show that for the operating conditions of the TEC, the temperature of the hot junctions of the TEM with an air heat sink does not go beyond the permissible limits. With a module power of 8 W, 12 W and 16 W, the temperature of the hot junctions of thermoelements stabilizes rather quickly and takes the value of 308 K, 313 K and 318 K. maintaining their stable temperature is most preferred is nickel nitrate, less - elaidic acid and paraffin. Calculations of the design of a device with a pre-cooled radiator system also show the efficiency of heat removal from the hot junctions of the TEM for the duration of the entire procedure for removing the IO from the human body.